Immunomodulation in Pediatric Asthma - Licari, Amelia; Manti, Sara; Castagnoli, Riccardo; Marseglia, Alessia; Foiadelli, Thomas; Brambilla, Ilaria; Marseglia, Gian Luigi (Frontiers in Pediatrics, 2019)
Childhood asthma is actually defined as a heterogeneous disease, including different clinical variants and partially sharing similar immune mechanisms. Asthma management is mainly focused on maintaining the control of the disease and reducing the risk of adverse outcomes. Most children achieve good control with standard therapies, such as low doses of inhaled corticosteroids and/or one or more controller. These medications are targeted to suppress bronchial inflammation and to restore airway responsiveness. However, they are not disease-modifying and do not specifically target inflammatory pathways of asthma; in addition, they are not significantly effective in patients with severe uncontrolled asthma. The aim of this review is to update knowledge on current and novel therapeutic options targeted to immunomodulate inflammatory pathways underlying pediatric asthma, with particular reference on biologic therapies.